2012
DOI: 10.5713/ajas.2012.12125
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Purple-fleshed Sweet Potato (Ipomoera batatas Cultivar Ayamurasaki) Powder Addition on Color and Texture Properties and Sensory Characteristics of Cooked Pork Sausages during Storage

Abstract: This study was conducted to evaluate the effects of adding purple-fleshed sweet potato (PFP) powder on the texture properties and sensory characteristics of cooked pork sausage. Sodium nitrite alone and sodium nitrite in combination with PFP were added to five different treatments sausages (CON (control) = 0.01% sodium nitrite, SP25 = 0.005% sodium nitrite and 0.25% purple-fleshed sweet potato powder combination, SP50 = 0.005% sodium nitrite and 0.5% purple-fleshed sweet potato powder combination, PP25 = 0.25%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
5
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
4
5
0
1
Order By: Relevance
“…Adding both sodium https://doi.org/10.5187/jast.2020.62.5.702 nitrite and PP affected the whiteness values of the sausages, because the SP1 and SP2 samples were whiter than all other treated samples (p < 0.05). These results agreed with those of Jin et al [24], who showed that adding NaNO 2 positively affected sausage whiteness. As shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Adding both sodium https://doi.org/10.5187/jast.2020.62.5.702 nitrite and PP affected the whiteness values of the sausages, because the SP1 and SP2 samples were whiter than all other treated samples (p < 0.05). These results agreed with those of Jin et al [24], who showed that adding NaNO 2 positively affected sausage whiteness. As shown in Fig.…”
Section: Discussionsupporting
confidence: 93%
“…The VBN content was comparable between the SP2 and CON groups, and lower in the PP2 than in the CON group on days 10 and 20 (p < 0.05). These findings agree with those of [23,24]. The low VBN values in the sausages were due to antimicrobial properties of PP.…”
Section: A-dsupporting
confidence: 90%
See 1 more Smart Citation
“…Contudo, o excesso de consumo desses aditivos tem causado preocupação na comunidade científica, em virtude dos efeitos nocivos à saúde humana (7) , relacionados à formação de compostos químicos cancerígenos, como nitrosaminas e nitrosamidas (8) , algumas das quais que apresentam, além da atividade carcinogênica, a mutagênica, a teratogênica e a embriopática (9) . Outro efeito nocivo se refere à metemoglobinemia ou síndrome do bebê azul, em que o nitrito, quando está presente no organismo, especialmente no infantil, age sobre a hemoglobina, oxidando o íon ferro (II) e íon ferro (III), impedindo assim a função normal da hemoglobina de transportar oxigênio, doença que pode levar à anóxia e morte (10)(11)(12) .…”
Section: Introductionunclassified
“…During cooking, nitrite can combine with secondary amines and amino acids in meat products and form N-nitroso compounds( e.g. nitrosamines) having health risks including allergic effects, vasodilator effects, metmyoglobin production, and production of carcinogenic nitrosamines (8). Recently, consumers have developed a stronger negative view towards artificial additives; therefore, the industry, researchers and official bodies are trying to respond to current consumer demands.…”
mentioning
confidence: 99%